2022
DOI: 10.1111/plb.13449
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi: Effects on secondary metabolite accumulation of traditional Chinese medicines

Abstract: Traditional Chinese medicine (TCM) has played a pivotal role in maintaining the health of people, and the intrinsic quality of TCM is directly related to the clinical efficacy. The medicinal ingredients of TCM are derived from the secondary metabolites of plant metabolism and are also the result of the coordination of various physiological activities in plants. Arbuscular mycorrhizal fungi (AMF) are among the most ubiquitous plant mutualists that enhance the growth and yield of plants by facilitating the uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 88 publications
0
10
0
1
Order By: Relevance
“…Secondary metabolites are the material basis of the quality evaluation of traditional Chinese medicinal plants. Studies have revealed that AM fungi (AMF) can promote host plant growth and increase the accumulation of secondary metabolites by the response mechanisms of plant hormones, nutritional elements and expression of key enzymes ( Ran et al, 2022 , Zhao et al, 2022 ). Zhu et al found that symbiotic fungi can affect the accumulation of sugars and alcohol-soluble components in stems of D. officinale ( Zhu et al, 2016 ).…”
Section: How Does Orm Benefit Host Plants?mentioning
confidence: 99%
“…Secondary metabolites are the material basis of the quality evaluation of traditional Chinese medicinal plants. Studies have revealed that AM fungi (AMF) can promote host plant growth and increase the accumulation of secondary metabolites by the response mechanisms of plant hormones, nutritional elements and expression of key enzymes ( Ran et al, 2022 , Zhao et al, 2022 ). Zhu et al found that symbiotic fungi can affect the accumulation of sugars and alcohol-soluble components in stems of D. officinale ( Zhu et al, 2016 ).…”
Section: How Does Orm Benefit Host Plants?mentioning
confidence: 99%
“…lebih dialokasikan pada pembentukan rimpang dan produksi kurkumin dari pada dialokasikan ke pertumbuhan tajuk, sedangkan pada perlakuan A. niger tunggal maupun inokulasi ganda lebih cenderung diarahkan untuk pertumbuhan tajuk dan pembentukan anakan. Machiani et al (2022) dan Ran et al (2022) melaporkan bahwa CMA pada tanaman obat dapat meningkatkan metabolit primer dan sekunder dengan mekanisme langsung melalui peningkatan penyerapan nutrisi dan air dan peningkatan kapasitas fotosistesis, atau secara tidak langsung dengan menstimulai produksi metabolit sekunder melalui perubahan konsentrasi fitohormon dan produksi molekul sinyal. CMA juga dilaporkan meningkatkan potensi alelopati dan kemampuan berkompetisi melalui peningkatan produksi metabolit sekunder pada 3 spesies gulma (Rashidi et al 2022).…”
Section: Pengaruh Inokulasi Cendawanunclassified
“…In the context of soil salinity, AMF plays a critical role in helping plants tolerate this stressor, mitigating its adverse effects on plant growth and health [ 12 ]. AMF symbiosis has also been shown to boost the production of secondary metabolites in traditional Chinese plants [ 13 ], medicinal plants [ 14 ], aromatic plants [ 15 ] which often have beneficial effects on plant health, defense against pests and pathogens, and potential human health benefits [ 13 ]. AMF also offers protective effects against soil contamination from heavy metals and other pollutants, while also enhancing soil physiochemical characteristics like nutrient cycling and organic matter decomposition, thereby promoting overall soil health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%